Head Teachers Leadership Style and Teachers' Job Satisfaction: A Comparative Analysis in Public and Private School - Sanam Javed; Munwar Bagum (Indus Journal of Social Sciences, 2025)
This study investigates the relationship between head teachers' leadership styles and teachers’ job satisfaction, offering a comparative analysis between public and private schools. Recognizing the pivotal role of leadership in shaping school environments, the research examines how different leadership approaches namely transformational, transactional, and laissez-faire impact teacher morale, motivation, and overall job contentment. The study is grounded in the belief that effective leadership not only influences academic performance but also determines the well-being and professional satisfaction of teachers. Data were collected through structured questionnaires and interviews from a sample of teachers and head teachers in both sectors. The findings reveal notable differences: transformational leadership, more commonly observed in private schools, is strongly associated with higher levels of teacher satisfaction due to its emphasis on vision, support, and professional growth. Conversely, public schools exhibited a mix of transactional and bureaucratic leadership styles, which often correlated with lower satisfaction levels due to limited autonomy and recognition. The study also identifies factors such as administrative support, workload, communication, and opportunities for professional development as significant mediators between leadership style and job satisfaction. The research underscores the need for targeted leadership training and policy reforms aimed at enhancing teacher satisfaction and retention across all types of educational institutions.